The image of a lady on horseback in 18th c. Russian culture. On the typology of equestrian portraits - Chezhina, Yuliya I. (Actual Problems of Theory and History of Art, 2012)
The paintings are analyzed and considered from the standpoint of contents, stressing the novelty of the subject in the art of the epoch. Much attention is given to the iconographic peculiarities of portraits.
Keywords: horsewoman; portrait; equestrian; culture; iconography; typology; Haute école; symbolics